Bargaining around the hearth - Pollak, Robert A. 1938- (National Bureau of Economic Research, 2007)
In "Unpacking the Household: Informal Property Rights Around the Hearth" (Yale Law Journal, 2006) Robert Ellickson argues that as long as members of a household expect their relationship to continue, norms, rather than law, will determine allocations among them. More specifically, Ellickson argues that in "midgame" household members either ignore the "endgame" completely or, if they do take endgame considerations into account, the relevant endgame considerations are determined by norms rather than by law. This paper examines the fit between Ellickson's claims and four bargaining models that economists have used to understand interactions within household and families.
Literaturverz. S. 11